2012
DOI: 10.1080/09712119.2012.672310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of growth performance, egg production, egg characteristics and haemato-biochemical parameters ofDesi, Fayoumi and Rhode Island Red chicken

Abstract: A total of 2001 un-sexed day-old chicks of each Desi, Fayoumi and Rhode Island Red (RIR) breeds were obtained from hatchery of Poultry Research Institute, Rawalpindi. The birds were maintained on deep litter system for a period of 72 weeks. In floor pens, each breed was reared separately in a single pen until seven weeks of age when 2001 birds were randomly distributed between pens, with 21 to 24 birds of the same breed per pen (2.00 to 2.50 ft 2 /bird). The results revealed that the average day-old weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
8
14
2
Order By: Relevance
“…This is higher than values reported by Islam et al (2014) for the Vanaraja breed, namely 48.32 ± 0.21 g at 32 weeks, and 53.07 ± 0.24 g at 40 weeks old,and an indigenous breed, namely 27.85±0.04 g at 32 weeks and 32.06 ± 0.07 g at 40 weeks old, all reared under an extensive system. Similarly, Khawaja et al (2012) reported average egg weights of 44.42 g, 43.35 g, and 56.83 g for Desi, Fayoumi and Rhode Island Red (RIR) breeds of chicken, respectively, reared up to 72 weeks old, which were comparatively lower than values recorded by the Boschveld chickens. Although the Boschveld birds came into lay at 21 weeks old (147 days), the Varanaja, an indigenous breed of India, and the Rakai, an indigenous breed of Uganda, came into lay at 187.45, 201.31 and 154 days, respectively (Islam et al, 2014;Roothaert et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This is higher than values reported by Islam et al (2014) for the Vanaraja breed, namely 48.32 ± 0.21 g at 32 weeks, and 53.07 ± 0.24 g at 40 weeks old,and an indigenous breed, namely 27.85±0.04 g at 32 weeks and 32.06 ± 0.07 g at 40 weeks old, all reared under an extensive system. Similarly, Khawaja et al (2012) reported average egg weights of 44.42 g, 43.35 g, and 56.83 g for Desi, Fayoumi and Rhode Island Red (RIR) breeds of chicken, respectively, reared up to 72 weeks old, which were comparatively lower than values recorded by the Boschveld chickens. Although the Boschveld birds came into lay at 21 weeks old (147 days), the Varanaja, an indigenous breed of India, and the Rakai, an indigenous breed of Uganda, came into lay at 187.45, 201.31 and 154 days, respectively (Islam et al, 2014;Roothaert et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…The FCR, which is the ratio of feed intake and bodyweight gain, indicated a low value, and FE, which is the ratio of bodyweight gain and feed intake, also showed a low value. Khawaja et al (2012) reported FCR ranging from 3.5 to 7.5 in Desi, Fayoumi and RIR breeds of chicken, with higher values at the growing stage, and lower values at the production stage. These values are higher than those of the animals used in this study, even as the average weight of the birds at 0-20 weeks of lay was 1.23 kg, while the Boschveld was 2.38 kg at 44 weeks of lay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations